Kebijakan Akses dan Layanan Arsip di Kantor Perpustakaan, Arsip dan Dokumentasi (KPAD) Kota Bukittinggi - Sari, Winda Musfita; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
Access policies and archive service aims to: (1) Make archival material can be accessed by the user, both for official as well as serve the needs of the public by using the archive depot repenstatif but at this point has not been performing well., (2) low human resources, because the officer who manages the archive does not have the educational background of archival science is able to carry out operational tasks in accordance with the demands that it should, so the archivists have not fully participate in serving visitors to find the information needed. Therefore it is advised: (1) the library should dare budgeted for security archive using the archive depot repenstantif unused in the Office of Libraries, Archives and Documentation of Bukittinggi, (2) Office of Libraries, Archives and Documentation Bukittinggi should propose additional staff records of archival science educational background to the area staffing agency (BKD), because workers archival science background knowledge about the intricacies of the parent organization in which he works; archivists must actively serving visitors to find the information needed. Keyword: access policies; archive service; Â archive